John Knox - Percy of Newcastle, Eustace Percy, Baron, 1887-1958. (Cambridge : The Lutterworth Press, 2013)
John Knox has suffered in this century from that trick of the popular imagination that seizes on one aspect of a historical figure and elevates it into the whole man. At one time he was the foremost Scottish genius, but in our day there have been those who would have us believe that he was a ranter, an iconoclast and perhaps a hypocrite. The Author of this classic biography has sought to find the truth between these two extremes. He shows us Knox against the disturbed currents of the Continent, where mediaeval Christendom was at an end and no new order had yet emerged from the chaos of creeds.
Chapter XXIV: The Last Campaign (August 1562-August 1565)1; 2; 3; 4; 5; 6; Chapter XXV: The Long Leave-Taking August 1565-November 1572; 1; 2; 3; 4; 5; 6; Back cover.
Online resource; title from PDF title page (ebrary, viewed November 29, 2013).
Master record variable field(s) change: 072
Keywords: Knox, John, -- approximately 1514-1572.; Knox, John, -- approximately 1514-1572.; Reformation -- Scotland; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; Reformation; Scotland; BIOGRAPHY & AUTOBIOGRAPHY / Religious; Electronic books